2015
DOI: 10.1002/14651858.cd007863.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal cardiotocography for fetal assessment

Abstract: BackgroundCardiotocography (CTG) is a continuous recording of the fetal heart rate obtained via an ultrasound transducer placed on the mother's abdomen. CTG is widely used in pregnancy as a method of assessing fetal well-being, predominantly in pregnancies with increased risk of complications. ObjectivesTo assess the effectiveness of antenatal CTG (both traditional and computerised assessments) in improving outcomes for mothers and babies during and after pregnancy. Search methodsWe searched the Cochrane Pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 61 publications
0
88
0
1
Order By: Relevance
“…The system 8000 is still commercially available from Huntleigh (who acquired Sonicaid in the 1990s) but to date no other manufacturer has adopted a similar approach, and antenatal computerised fetal heart rate analysis has not been widely adopted, because of the difficulty of predicting the cases in which it might be useful. The 2012 Cochrane systematic review of antenatal cardiotocography included only six randomised studies involving 2105 women, and these were mostly of poor quality . The meta‐analysis was therefore underpowered to assess potentially preventable deaths; there were only two studies in which this aspect could be assessed, and the relative risk of 0.23 had 95% confidence intervals from 0.04 to 1.29.…”
Section: Practical Implementation Of Computerised Antenatal Cardiotocmentioning
confidence: 99%
“…The system 8000 is still commercially available from Huntleigh (who acquired Sonicaid in the 1990s) but to date no other manufacturer has adopted a similar approach, and antenatal computerised fetal heart rate analysis has not been widely adopted, because of the difficulty of predicting the cases in which it might be useful. The 2012 Cochrane systematic review of antenatal cardiotocography included only six randomised studies involving 2105 women, and these were mostly of poor quality . The meta‐analysis was therefore underpowered to assess potentially preventable deaths; there were only two studies in which this aspect could be assessed, and the relative risk of 0.23 had 95% confidence intervals from 0.04 to 1.29.…”
Section: Practical Implementation Of Computerised Antenatal Cardiotocmentioning
confidence: 99%
“…The two previous sentences, ‘The meta‐analysis was therefore underpowered to assess potentially preventable deaths; there were only two studies in which this aspect could be assessed, and the relative risk of 0.23 had 95% confidence intervals from 0.04 to 1.29. Although the relative risk is encouraging, the numbers are clearly too small to conclude that antenatal monitoring per se is beneficial’, correctly reflect the findings of the referenced Cochrane review.…”
mentioning
confidence: 58%
“…These last two trials had the additional problem that since traditional CTG had not been shown to be effective, even well‐designed trials would have been difficult to interpret. It is hardly surprising that 35 years later the Cochrane review of antenatal CTG still concludes: ‘There is no clear evidence that antenatal CTG improves perinatal outcome’ …”
Section: What Has Happened Since In Research?mentioning
confidence: 99%